The Fundamental Elements of Strategy Concepts, Theories and Cases - Yu, Xiu-bao.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2021)
This open access book clarifies confusions of strategy that have existed for nearly 40 years through the core thoughts of three fundamental elements. Unlike the traditional definition of strategy as "a plan to achieve a long-term goal from overall considerations(3y(Bin a linear view, this book defines strategy from non-linear viewpoint as it is in the real world. The art of a strategy lies not only in the determination of development goals, but also in the identification of development problems and putting forward overall guiding ideology of solving problems. Rich illustrations as well as numerous business and military cases are presented in helping readers to understand the fundamental elements of strategy. The general scope of the book includes introductions to the three fundamental elements of strategy, three-sub decisions of a complete strategic decision, incomplete strategies, relationship between tactic and strategy, three elements of competitive and corporative strategies. There may be biases in company-level, real strategic decision-making which makes a complete strategy not necessarily a perfect one. The book introduces biases and reasons for the biases, helping industrial strategic decision-makers understand the importance of knowing the nature of the company, the industry and its environment. In addition, this book also presents principles and evaluation approaches of strategic decisions, explores the reasons for the excessive definitions of the strategy concept, and discusses directions of future$1 (Bs research tasks. The book will benefit business managers who are interested in knowing what a complete strategic decision is and how to avoid errors or biases in strategic decision-making. It also benefits students in business schools (especially in MBA/EMBA programs) who are (or will be) on executive positions. Academic researchers may find it is interesting to understand strategy from the view of the three elements.The new view provides a novel insight into strategy and promotes several research directions in the future. The three elements of strategy are also applicable to military strategies and readers who are interested in military and may find its value as well.s
Chapter 1. Introduction - What goes wrong in our understanding of the strategy concept? -- Chapter 2. Why are there over 90 definitions of the strategy concept? -- Chapter 3. Fundamental Elements of the Strategy Concept -- Chapter 4. What is an Organizational Strategic Decision? -- Chapter 5. Tactics and the Three Elements of Strategy -- Chapter 6. Firm Strategies and Their Three Elements -- Chapter 7. Strategic Decision Biases and Decision Making Principles -- Chapter 8. Knowing Yourself and Knowing the Others -- Chapter 9. Strategic Evaluation Based on Three Elements -- Chapter 10. Implications for Future Research.
Keywords: Management; Operations research; Business; Management science; Management; Operations Research and Decision Theory; Business and Management